2020
DOI: 10.1016/j.metabol.2020.154137
|View full text |Cite
|
Sign up to set email alerts
|

Time for a paradigm shift in treating type 1 diabetes mellitus: coupling inflammation to islet regeneration

Abstract: Type 1 diabetes mellitus (T1DM) is an autoimmune disease that targets the destruction of islet beta-cells resulting in insulin deficiency, hyperglycemia and death if untreated. Despite advances in medical devices and longer-acting insulin, there is still no robust therapy to substitute and protect beta-cells that are lost in T1DM. Attempts to refrain from the autoimmune attack have failed to achieve glycemic control in patients highlighting the necessity for a paradigm shift in T1DM treatment. Paradoxically, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 147 publications
(181 reference statements)
3
25
0
Order By: Relevance
“…This growth factor along with a subset of genes implicated in cytoskeletonintegrin connection previously shown to be involved in wound healing were down regulated in siHMG20A treated astrocytes. Taken together these molecular data further support our model that HMG20A likely potentiates the degree of astrogliosis promoting an anti-inflammatory and pro-regenerative phenotype, analogous to our recent studies establishing the role of the orphan nuclear receptor LRH-1/NR5A2 in immunomodulation and trans-regeneration of islet beta cells [39,67,68].…”
Section: Discussionsupporting
confidence: 89%
“…This growth factor along with a subset of genes implicated in cytoskeletonintegrin connection previously shown to be involved in wound healing were down regulated in siHMG20A treated astrocytes. Taken together these molecular data further support our model that HMG20A likely potentiates the degree of astrogliosis promoting an anti-inflammatory and pro-regenerative phenotype, analogous to our recent studies establishing the role of the orphan nuclear receptor LRH-1/NR5A2 in immunomodulation and trans-regeneration of islet beta cells [39,67,68].…”
Section: Discussionsupporting
confidence: 89%
“…Remarkably, in a mouse model of experimental autoimmune diabetes, BL001-mediated β-cell regeneration occurred concomitantly with the expansion of the anti-inflammatory Tregs and T helper 2, and primed macrophages towards the immunosuppressive and tissue remodeling M2 phenotype [82]. Interestingly, the abundance of the bihormonal INS+/GCG+ cells after BL001 treatment in this mouse model was markedly higher than in the STZ model, indicating the important contribution of Tregs and M2 macrophages in αto β-cell transdifferentiation [82,84]. Supporting this immunecoupled β-cell regeneration, the combined therapy of induction of MHC-mismatched mixed chimerism to attenuate the immune response together with gastrin and EGF administration resulted in β-cell regeneration and glucose homeostasis recovery in firmly established diabetic NOD mice [85].…”
Section: Can Gaba Stimulate αTo β-Cell Transdifferentiation?mentioning
confidence: 78%
“…Lineage-tracing studies revealed that αto β-cell transdifferentiation is the major source of β-cells, which only reaches these levels of activation after attenuation of the immune response [85]. This integrated non-mutually exclusive and mandatory islet-immune dialogue may provide some clues on failures of clinical trials targeting solely the immune system, which will likely compromise β-cell replenishment [84,86].…”
Section: Can Gaba Stimulate αTo β-Cell Transdifferentiation?mentioning
confidence: 99%
“…Singh et al [27] explained serological, biochemical, and genetic aspects related to gene HLA-DQB1 and its association with the T1DM. Nadia et al [28] explained the paradigm shift in treating T1DM by coupling inflammation to islet regeneration. Buzzetti et al [29] comprehensively explained the role of obesity in the increasing incidence of T1DM around the globe.…”
Section: Current Treatment Modalities Available For Diabetes In Medicinementioning
confidence: 99%